Intensified Surveillance and Insecticide-based Control of the Chagas Disease Vector Triatoma infestans in the Argentinean Chaco - Gurevitz, Juan M. (Public Library of Science, 2013)
BACKGROUND: The elimination of Triatoma infestans, the main Chagas disease vector in the Gran Chaco region, remains elusive. We implemented an intensified control strategy based on full-coverage pyrethroid spraying, followed by frequent vector surveillance and immediate selective insecticide treatment of detected foci in a well-defined rural area in northeastern Argentina with moderate pyrethroid resistance. We assessed long-term impacts, and identified factors and procedures affecting spray effectiveness. METHODS AND FINDINGS: After initial control interventions, timed-manual searches were performed by skilled personnel in 4,053 sites of 353–411 houses inspected every 4–7 months over a 35-month period. Residual insecticide spraying was less effective than expected throughout the three-year period, mainly because of the occurrence of moderate pyrethroid resistance and the limited effectiveness of selective treatment of infested sites only. After initial interventions, peridomestic infestation prevalence always exceeded domestic infestation, and timed-manual searches consistently outperformed householders' bug detection, except in domiciles. Most of the infestations occurred in houses infested at baseline, and were restricted to four main ecotopes. Houses with an early persistent infestation were spatially aggregated up to a distance of 2.5 km. An Akaike-based multi-model inference approach showed that new site-level infestations increased substantially with the local availability of appropriate refugia for triatomine bugs, and with proximity to the nearest site found infested at one or two preceding surveys. CONCLUSIONS AND SIGNIFICANCE: Current vector control procedures have limited effectiveness in the Gran Chaco. Selective insecticide sprays must include all sites within the infested house compound. The suppression of T. infestans in rural areas with moderate pyrethroid resistance requires increased efforts and appropriate management actions. In addition to careful, systematic insecticide applications, housing improvement and development policies that improve material conditions of rural villagers and reduce habitat suitability for bugs will contribute substantially to sustainable vector and disease control in the Gran Chaco.